TAMAN BACA DI BANJARBARU - Mufidah, Husnun Zahidatul; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Reading is one of the basic skills that must be mastered by everyone. However, the reading rate of people in Indonesia is very low. In fact, literacy conditions in Indonesia are now in crisis, which is also called a literacy emergency. Increasing interest in reading in the younger generation in Indonesia today is really important amidst so many technologies that are very rapidly developing. Therefore, Indonesia is currently so active at making movements to increase interest in reading. The purpose of this Community Library is to increase the reading interest of Indonesian people while providing adequate facilities for reading for the community. The design of Community Library uses architectural programming method. The process of this method is divided into two stages consisting of preparing a program that is an activity of analyzing data that led to architectural problems and designing designs that can solve problems. The digitalization of books can be used as a way to increase the children and adults interest in reading again. However, that still feels lacking, because it requires a more efficient steps that can further influence the interest in reading and attract the attention of the public to e interested in reading. One way to attract the reading interest of public to be interested in reading is to turn the library into a creative reading place. This is what underlies the thought of the Community Library. Creating a Community Library with the concept of Recreation Space is expected to help change people's view of reading which was boring to be fun. The design is a comfortable, varied, and fun reading space with complete facilities.